Pengaruh Karakteristik Pekerja terhadap Produktivitas Proyek Pembangunan Gedung Kantor Bahasa Provinsi Maluku: The Influence of Worker Characteristics on the Productivity of the Maluku Language Office Building Constructions Project - Tomia, Fitria; Sahusilawane, Tonny; Abdin, Maslan (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Along with developments in time and technology, many construction projects are growing rapidly, ranging from small to large construction projects. This development increases competitiveness between construction project companies. All of these human resource potentials influence the organization's efforts to achieve its goals. Human resource management is the right solution for companies to increase the productivity of employees in the company. To support the research results, the research data (questionnaire) obtained will be analyzed using statistical tools with the help of the SPSS (Statistical Product and Service Solution) program version 26.0. Techniques for data analysis in this research are validity test, reliability test, T test and F test. The results of observations in the field on the Maluku Province Language Office building construction project, the workforce lacks discipline in working because it has a dominant influence on work productivity, and the results of observations in the field on the construction project of the Language Provincial Language Office building are Discipline (X1), environmental factors (X2) and skills (X3) greatly influence work productivity.